2014
DOI: 10.1002/uog.13217
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal unilateral cerebellar hypoplasia in a series of 26 cases: significance and implications for prenatal diagnosis

Abstract: Objective To define imaging patterns of unilateral cerebellar hypoplasia (UCH), discuss possible pathophysiological mechanisms and underline the etiology and prognosis associated with these lesions. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…Thus, this represents a challenge to precisely predict outcome in prenatally identified cerebellar hypoplasia. A normal outcome was mainly related to normal karyotypes, mild lesion, and intact vermis . It seems that an intact vermis is related to normal outcome and no truncal ataxia, whereas involvement of the cerebellar vermis is associated with a poorer cognitive outcome.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, this represents a challenge to precisely predict outcome in prenatally identified cerebellar hypoplasia. A normal outcome was mainly related to normal karyotypes, mild lesion, and intact vermis . It seems that an intact vermis is related to normal outcome and no truncal ataxia, whereas involvement of the cerebellar vermis is associated with a poorer cognitive outcome.…”
Section: Discussionmentioning
confidence: 91%
“…The outcome of fetuses with cerebellar hypoplasia is variable, ranging from almost normal development to serious developmental impairment. 14,15 Thus, this represents a challenge to precisely predict outcome in prenatally identified cerebellar hypoplasia. A normal outcome was mainly related to normal karyotypes, mild lesion, and intact vermis.…”
Section: Associated Copy Number Variations Among Fetuses Of Cerebelmentioning
confidence: 99%
“…Increasing experience with prenatal US and fetal MR imaging has demonstrated that unilateral cerebellar hypoplasia is of prenatal origin (and thus represents a disruption), with hemorrhage as the leading cause (5,79).…”
Section: Unilateral Cerebellar Hypoplasiamentioning
confidence: 99%
“…In case of an ischemic-hemorrhagic parenchymal insult, the localization of the lesion impacts on the prognosis: for instance, a unilateral anterior frontal lesion, if limited, can carry a good prognosis, a unilateral cerebellar hemispheric insult may also have a good outcome if the vermis is not involved [27,28]. Lesions involving the cortex are at risk for postnatal focal epilepsy; if the central sulcus is involved, a contralateral congenital hemiparesis is the rule (fig.…”
Section: Localized Parenchymal Ischemic-hemorrhagic Lesionsmentioning
confidence: 99%